A VISUALIZATION APPROACH FOR COMPARING FINANCIAL PERFORMANCE OF PHARMACEUTICAL COMPANIES - GUPTA, DR. SUCHITA; KOTWANI, DR. SHALU (The journal of contemporary issues in business and government, 2022)
Pharmaceutical industry of India is grooming with fast rate. It is estimated at US 42 billion and growth is expected to continue in future. Indian Pharmaceutical companies are among the few companies who have come up with Covid 19 medicines and vaccines. These companies not only serving India but also other countries. Glenmark pharmaceutical was the first company to introduce oral drug for curing Covid 19, then some other companies like Cipla Ltd, Sun Pharmaceutical Industries, Best Biotech, Intas Pharmaceutical and so on also produces oral drug for the treatment of Covid 19. Past two years were phenomenal in terms of business and growth, many sectors have shown fluctuations due to pandemic, pharmaceutical sector also got affected by it to some extent, but have come with positive growth in last FY that is 2020-21. With the rapid changing business environment it is essential to measure the financial performance of the firm for long term sustainability. The financial data is so scattered that it is not possible for a layman to extract the vital information from them. It also delays the important decisions on the part of the various stakeholders. Although there are numerous statistical and financial techniques are available to analyse the financial data, but all these techniques are complex and difficult to understand by a layman. This leads to the need of the simple technique that helps to analyse financial data easily. Now a day’s visualization is adopted whole heartedly by researchers and professionals to present the financial information in simplified manner. Visualization software like tableau, Power BI, Sisense are used by the professionals worldwide The study evaluates the financial performance of top five pharmaceutical companies selected on the basis of their market capitalization. The study is exclusive as it applies data visualization techniques through Tableau software to analyse the performance and interpret the results.